Occupational Safety Study Of Machinery Usage In A Manufacturing Plant - Saliza, Esa (2025)
This study examined safety awareness, machinery hazards and risk management in an electronics manufacturing plant in Malaysia. The Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methodology was used to identify potential hazards, evaluate risk levels, and assess existing control measures. A questionnaire survey was conducted among workers to assess safety awareness regarding seven key Occupational Safety and Health (OSH) factors: safety and health policy, standard operating procedures (SOP), equipment, training, safety and health committee, commitment and attitude, and environmental conditions. The findings revealed variations in awareness and compliance, with certain aspects requiring improvement, such as training and safety committee involvement. Observations identified mechanical hazards, including pinch points and sharp edges, and non-mechanical hazards like noise and electrical risks. Risk assessments revealed that whereas certain risks were effectively controlled, others needed additional mitigation to lower the likelihood and severity of events. Following the hierarchy of controls, control methods were suggested, including the use of personal protective equipment (PPE), administrative controls like supervision and training, and engineering controls like safety guards. The study underlined the necessity of ongoing risk assessments and planned safety measures to reduce the hazards associated with machinery and enhance worker safety in the manufacturing sector.